Implementasi Sistem Informasi Peringkat Akademik Mahasiswa Dengan Metode Ahp Berbasis Web Dengan Arsitektur Model View Controller - Woro Isti Rahayu; Ahmad Afif Raihan; Fazli Ihsan Priyadi; Noviana Riza (Data Sciences Indonesia (DSI), 2026)
Advances in information technology in the world of education have led to digital transformation, especially in the management of student academic data. This project focuses on developing a student academic ranking information system that use the Analytical Hierarchy Process (AHP) method as the basis for ranking structure to support system development so that the files created are more structured.Flask framework is utilized as the backend foundation using Python, integrated with MySQL for database management. The user interface is built with HTML and CSS to ensure a simple yet interactive design. The system allows users to input grades, automatically calculate GPA and semester performance, and determine academic rankings based on criteria weighted using the AHP method. This system is expected to help students monitor and evaluate their academic progress independently in an organized and efficient manner. In addition, this project serves as a learning platform for student developers to apply the knowledge they have gained in the fields of software engineering, data management, and programming logic.